Meta-Analysis of Group Mindfulness-Based Cognitive Therapy for Decreasing Symptoms of Acute Depression. Issue 1 (2nd January 2016) - Lenz, A. Stephen; Hall, Joseph; Bailey Smith, Laura
Abstract : We implemented a meta-analysis of randomized trials to estimate the treatment effect of mindfulness-based cognitive therapy in a group format compared to no treatment or alternative group interventions. We inspected moderators of effect size and estimated treatment effects over time across 31 studies with yielded mean effect sizes revealing large and medium effects for no treatment and alternative treatment comparisons, respectively. Moderator analyses revealed differential models for explaining variations in treatment effects related to age, percentage of men in studies, domicile, study setting, and type of alternative treatment comparison. Implications for group work and limitations of this study are discussed.